Pelo rio Mapuera: Reflexões sobre arqueologia e etnologia indígena na Amazônia e Guiana - Camila Pereira Jacome (2011)
This work intends to contribute to the archaeological and ethnological scholarship engaged with discussing long-term relationships and internal and external policies among the indigenous populations of the Amazon region. Ethnographers argue that there are two main conflicting visions concerning that topic: one of them claims that there are intense relations between different groups, linked by extensive political, trading, and kinship networks (Gallois 2005). The other favors notions of atomism and political isolation among indigenous groups (Rivière 1984). The example of the Waiwai Indians (Mapuera River northern Pará) with whom we have been working since, allows us to demonstrate how both modes work together and operate synchronously in a complementary manner. Some ethnographers (Lathrup 1970, Roosevelt 1980) argue that chiefdoms already existed in the prehistoric period, while others contend that if that were the case, large populations development and sustainability would not be possible in the rainforest. Our project attempts at overcoming this quandary by looking at both modern indigenous societies and archaeological remains to better understand the societies of this region In order to examine if these modalities existed before the European colonization, we peruse and discuss the most recent archeological scholarship concerning the middle Amazon region (Neves, 2010; Moraes 2010, Lima 2009), more specifically the Tapajós and Trombeta regions (Gomes 2009; Guapindaia 2008), and alongside the coast of Guyana (Rostain 2010). The main disagreement between the two hypotheses relevant to some archaeologists (Lathrap 1970, Roosevelt 1980) concerns the existence or not of chiefdoms since the prehistoric period, and the observation made by anthropologists that suggests that the current population form small, autonomous societies. Such tension is a result of theoretical impasses and methodological differences as well as of difficulties of dialogue between the two disciplines. We have noted that the two fields of knowledge tend to conceive of indigenous political parties, past and present, as very dissimilar. Our conclusion therefore is that the absence of historical exchange between archeology and anthropology contributed to the lack of a productive debate on Amerindian societies of the past and present.